Epidemiology of cryptogenic fibrosing alveolitis in Moravia and Silesia - Kolek, Vítězslav (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1994)
Cryptogenic fibrosing alveolitis in Moravia and Silesia (4 million inhabitants) was evaluated using standard epidemiological and clinical parameters. During 1981-1990 the incidence of cryptogenic fibrosing alveolitis ranged from 0.74 to 1.28/100,000. The trend of incidence was increasing slightly. The prevalence rose from 6.5 to 12.1/100,000. The male/female ratio was 1:1.2; 54% of patients were less than 40 years old. Biopsy (mostly open lung biopsy) supported the diagnosis in 38% of cases. During 1981-1990 years 379 new cases were detected, 488 cases altogether were registered up to 1990. The death rate calculated by incidence and prevalence was 13% and 10% resp. The mean regional incidences varied from 0.34 to 2.69/100,000, regional prevalences varied from 4.1 to 27.6/100,000. No correlation with the regional incidences of sarcoidosis and tuberculosis was found. No significant differences in coal mining areas with a high occurrence of pneumoconiosis or in areas with developed agriculture were detected. Significantly higher values were found in the regions of the four major diagnostic centres: a mean incidence of 1.58/100,000 and a mean prevalence of 20.8/100,000 (p < 0.05). The results suggest that the level of diagnostic possibilities and efforts dominates over ecological and environmental factors in the detecting of cryptogenic fibrosing alveolitis.
Keywords: dospělí; Česká republika; Pulmonary Fibrosis; plicní fibróza; Incidence; prevalence; lidé; Female; mužské pohlaví; Prevalence; Male; incidence; Czech Republic; Adult; ženské pohlaví; Humans